Identifikasi Kandungan Bakteri Coliform Pada Air Es Batu Di Rumah Makan - Anggun Mutiara Sukma; Riyan Ningsih; Vivi Filia Elvira; Syamsir; Ayudhia Rachmawati (Buletin Keslingmas, 2025)
Coliform bacteria are an indicator of contamination in foodstuffs that can cause waterborne diseases such as diarrhea. Ice cubes are homemade food products produced only from water in plastic bags and then frozen. The increased risk of ice cube contamination can occur from the manufacturing process to serving buyers. This study aims to identify the presence of Coliform bacteria in ice cubes sold in restaurants in Jalan Pramuka, Samarinda City. This study used descriptive quantitative methods and the Most Probable Number (MPN) method for the analysis of ice cube water samples. Samples were taken from 22 restaurants and analyzed at the East Kalimantan Regional Health UPTD laboratory. The results showed that 86.4% of restaurants did not meet sanitary hygiene standards, and more than 50% of ice cube samples tested had Coliform bacteria counts exceeding the threshold set by Permenkes No. 2 Year 2023. These findings indicate the potential for serious health risks to consumers. Conclusions and suggestions from this study should improve sanitation supervision in the ice cube production process as well as education to sellers regarding the importance of hygiene in maintaining food quality. This study is expected to serve as a reference for authorities in sanitation policy making and increase public awareness of health risks due to Coliform bacteria contamination.